Uma interpretação do agir docente revelado por gestos didáticos e gestos de aprendizagem no contexto da Graduação e da Pós-Graduação - Cervera, Maria Christina da Silva Firmino (2015)
This thesis in Applied Linguistics area aims to investigate the didactic gestures (AEBY-DAGHÉ and DOLZ, 2008, SCHNEUWLY and DOLZ, 2009) used by the teacher in the teaching-learning of the genre academic review, in the university context, checking how student´s learning gestures are created. Justified the decision to investigate the didactic gestures due to the fact that these units can reveal the objects to be taught and take a didactic perspective, moreover, teaching gestures can be interpreters of how the teacher's work is done and how they can reveal in response to student´s learnings about the object of study. In addition, the didactic gestures can bring light to the teaching-learning process with a genre, focusing on the development of the object decomposition process to be taught in the course of activities of the strategies, teaching tools put to use by the teacher, and all these strategies could prove the real teacher's work. We also assume that the didactic gestures allow not only identify the acting teacher (MACHADO and BRONCKART, 2009), but also the embodiment of this act establishing interaction in the construction of knowledge of the student in the classroom. We recognize the act teaching as an occupation that consists on complex gestures that if described and understood, may give the profession a character, admittedly, more professional. We use also the notions about the review model Interactionism Sociodiscursivo (BRONCKART, [1999] 2007), acting teacher (MACHADO and BRONCKART, 2009), and didactic gestures (AEBY-DAGHÉ and DOLZ, 2008). The corpus of research was audio recordings and later three classes transcripts, two classes recorded on different days within a month, with graduate students, and a recorded class with graduate students, about five months after the first recordings, totaling approximately 4 hours of recordings. The participants are students of evening courses in São Paulo, two rooms of new students in a course of Directors, with an average of 70 students per class, graduation, and 09 students in the postgraduate course in a night Educational Psychology. Analyses of data from the transcripts were based on the ISD model of analysis in respect of two categories: the production context and the overall plan of the thematic content. Based on these categories, we find the didactic gestures that lead to understanding of the teacher's work and acting teacher with regard to the object of study. The methodological approach used was the qualitative approach (ANDRÉ, 1995), described in a case study strategy (ANDRÉ, 1995) focusing on the difficulties students have in academic writing of a specific academic genre. The results showed that the specific didactic gestures reveal the teachable dimensions of an object of study and the teaching-learning process, which can create learning gestures